Respuesta :
Answer:
Step-by-step explanation:
If you want to factor
[tex]m^2+11m=0[/tex], you could throw that into the quadratic formula with a = 1, b = 11 and c = 0, but the easier thing to do is to factor out what's common in those 2 terms. m is common, so when we factor it out:
[tex]m(m+11)=0[/tex]
That's the factored form.
By the Zero Product Property, either
m = 0 or m + 11 = 0.
So the 2 solutions to this are
m = 0 or m = -11
Not sure how far you need to go with this.
Answer:
m=0
m=-11
Step-by-step explanation:
To solve this question we will have to factorise to make it easy to solve
11m+m2=0
Ok
Let's solve
m(11+m)=0
m=0
When
11+m=0
Substrate 11 from both sides
m=-11
Therefore m=0 ,m=-11
Factorisation is the best way to solve this question so there final answer is m=0 and m=-11